Screening for the inhibitory effect of the crude extracts of Carica papaya L. and Chrysophyllum cainito L. on the growth of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa - Castillo, Arleen Grace R.; Catalya, Mary Joan Kristine C.; Cho, Joan S.; Delabajan, Jaysel R.; Mabulac, Marichu P. (1999)
Filter paper disc-agar diffusion method was used in determining the antibacterial effect of the bark, leaf and pulp extracts of Carica papaya L. and Chrysophyllum cainito L. Highest concentration of 16,000 ppm of the extract was observed to have inhibited greatly the growth of test bacteria. Results suggested that the bark, leaf and pulp extracts of C. papaya L. have inhibitory effect on the growth of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The bark and leaf extracts of C. cainito L. yielded the same results on the three test bacteria. Its pulp extract showed inhibition on the growth of E. coli and S. aureus but not on P. aeruginosa.
Research paper (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and Technology